Spatial patterns of microplastic contamination, Batophora occidentalis invasion, and physiological responses of Holothuria tubulosa from a Mediterranean coastal lagoon - Jessica Lombardo; Amanda Cohen-Sanchez; Montserrat Compa; Lorenzo Gil; Samuel Pinya; Silvia Tejada; Antoni Sureda (Environmental Pollution, 2026)

Spatial variation in isotopic niches and trophic structure of Callinectes sapidus in the Balearic Islands - Esperança Perelló; Antoni Sureda; Antoni Box; Montserrat Compa; Samuel Pinya (Estuarine, Coastal and Shelf Science, 2026)

Depth-dependent temperature shifts and their impact on zooxanthellae dynamics and physiological stress in Anemonia sulcata - Amanda Cohen-Sánchez; Montserrat Compa; Maria Magdalena Quetglas-Llabrés; Olaia Araujo; Silvia Tejada; Lorenzo Gil; Samuel Pinya; Antoni Sureda (Marine Environmental Research, 2026)

Invasive species management: The role of recreational fishing in managing Callinectes sapidus in the Balearic Islands, Spain - Esperança Perelló; Joan Terrassa; Antoni Sureda; Samuel Pinya; Montserrat Compa (Estuarine, Coastal and Shelf Science, 2026)

Physiological Stress Induced by an Invasive Filamentous Green Alga on a Native Sponge from a Coastal Mediterranean Lagoon (Balearic Islands) - Jessica Lombardo; Joseba Aguilo-Arce; Silvia Tejada; Lorenzo Gil; Samuel Pinya; Pere Ferriol; Antoni Sureda; Montserrat Compa (Journal of Chemical Ecology, 2025)

Presence and Potential Effect of Microplastics Associated with Anthropic Activity in Two Benthic Fishes Serranus scriba and Lithognathus mormyrus - Amanda Cohen-Sánchez; Juan Alejandro Sanz; Montserrat Compa; Maria Magdalena Quetglas-Llabrés; Maria del Mar Ribas-Taberner; Lorenzo Gil; Silvia Tejada; Samuel Pinya; Antoni Sureda (Fishes, 2025)
Plastic pollution poses a massive problem to the environment, particularly seas and oceans. Microplastics (MPs) ingestion by marine species can generate many adverse effects, including causing oxidative stress. This study evaluated the effects of anthropic activity-related MP presence in two coastal fish species—Serranus scriba (more related to rocky bottoms) and Lithognathus mormyrus (more related to sandy bottoms)—in two areas of Mallorca Island (Western Mediterranean) with varying anthropic pressures with similar mixed rocky/sandy bottoms. A total of eight fish samples per species and per area (total n = 32), as well as three water samples (500 mL each) and three sediment samples per area, were collected and analyzed. The results showed that despite plastic presence in both areas, the area with higher tourism affluence was also the most polluted. Fourier transform infrared spectroscopy analysis confirmed that the majority of recovered polymers were polyethylene and polypropylene. The pattern of MPs presence was reflected in the biomarker analysis, which showed higher values of antioxidants, namely catalase (CAT) and superoxide dismutase (SOD); detoxification, namely glutathione s-transferase (GST); and inflammation, namely myeloperoxidase (MPO)—enzymes in the gastrointestinal tract of fish from the more polluted area. However, no statistical differences were found for malondialdehyde (MDA) as a marker of lipid peroxidation. As for differences between species, S. scriba presented a higher presence of MPs and measured biomarkers than in L. Mormyrus, suggesting higher exposure. In conclusion, these results showed that increased anthropic activity is associated with a higher presence of MPs which, in turn, induces an adaptative response in exposed fish. Moreover, species living in the same area could be differentially affected by MPs, which is probably associated with different behavioural and feeding habits.

Microplastic filtering and its physiological effects on the Mediterranean bath sponge Spongia officinalis (Porifera, Demospongiae) - Joseba Aguilo-Arce; Montserrat Compa; Giuseppe Corriero; Maria Mastrodonato; Ilaria Savino; Daniela Semeraro; Antoni Sureda; Roberta Trani; Caterina Longo (Marine Pollution Bulletin, 2025)

Assessing heavy metal accumulation in the invasive blue crab (Callinectes sapidus): environmental and human health implications - Esperança Perelló; Samuel Pinya; Antoni Box; Antoni Sureda; Montserrat Compa (Environmental Science and Pollution Research, 2025)
Heavy metals are increasingly becoming a significant environmental concern, especially regarding food safety and security. This is especially concerning as the consumption of harvested marine species can pose potential health concerns. The arrival of the blue crab, Callinectes sapidus , to the Balearic Islands has led to the need to evaluate its environmental implications and potential as a food source as part of management efforts. In the present study, the concentrations of cadmium (Cd), lead (Pb), and mercury (Hg) in the muscle tissue of C. sapidus were evaluated at several locations in the Balearic Islands in the western Mediterranean Sea. A total of eighty-three blue crabs were examined (45 males and 38 females) and the concentrations of the heavy metals were evaluated. Regarding metal concentrations, overall, Hg was the most present followed by Cd and then Pb. Concentrations were also site dependent, with Es Grau having the highest Hg concentrations while in s’Albufereta the highest Cd concentrations were observed. Moreover, differences in metal accumulation were also observed between sexes, with juveniles and females exhibiting higher Cd concentrations than males. Furthermore, regarding potential human health concerns for consumption, the margin of exposure (MOE) for Pb were all above 1 and the estimated weekly ingestion (EWI) for Cd and Hg, were all below the established guidelines for food safety. These results highlight that the consumption of C. sapidus from the Balearic Islands does not currently pose a health risk the recreational fisheries sector. Considering these findings, the muscle tissue of C. sapidus is a valuable bioindicator for monitoring heavy metal levels, and continued site-specific monitoring is recommended for the coastal ecosystems of the Balearic Islands.

Oxidative stress response in native algae exposed to the invasive species Batophora occidentalis in S’Estany des Peix, Formentera (Balearic Islands) - Jessica Lombardo; Silvia Tejada; Montserrat Compa; Vicent Forteza; Lorenzo Gil; Samuel Pinya; Antoni Sureda (Frontiers in Marine Science, 2025)
Algae represent more than 41% of marine biological invasions worldwide. If non-native algae become an invasive and dominant species, they will inevitably affect the characteristics of the ecosystem. The study aimed to evaluate the potential effect of the recently arrived Batophora occidentalis growing over three native algae: Acetabularia acetabulum , Dasycladus vermicularis and Caulerpa prolifera in S’Estany des Peix (Formentera Island, Spain), a shallow saltwater lagoon environment, by means of antioxidant biomarkers. The environmental conditions of the lagoon favoured the extensive progression of B. occidentalis , which since 2020 has progressively been spreading to the entire perimeter of the lagoon where it has found a substrate to attach itself to, even epiphytize native algae. The activities of the antioxidant enzymes (catalase, superoxide dismutase, and glutathione reductase), the phase II detoxification enzyme glutathione S -transferase and levels of malondialdehyde (as an indicator of lipid peroxidation) were evaluated. The results showed significant increases in all monitored biomarkers in the three native algae affected by B. occidentalis , with notable elevations in antioxidant enzyme activities and detoxification response. However, MDA levels increased only in A. acetabulum and D. vermicularis , but not in C. prolifera , suggesting that the latter species exhibits greater resistance to lipid peroxidation. These findings indicate that native algae experience biochemical stress, likely induced by competition or environmental changes caused by B. occidentalis . In conclusion, the presence of the invasive alga B. occidentalis can induce a stressful situation in epiphytized native algae, as evidenced by an increase in oxidative stress biomarkers. Further studies are needed to assess its potential effects on the growth and survival of the affected algae, as well as its ecological impact on the ecosystem.

Posidonia oceanica egagropiles: Good indicators for plastic pollution in coastal areas? - Carme Alomar; Montserrat Compa; Valentina Fagiano; Margherita Concato; Salud Deudero (Regional Studies in Marine Science, 2024)

A meta-analysis of potential biomarkers associated with microplastic ingestion in marine fish - Montserrat Compa; Xavier Capó; Carme Alomar; Salud Deudero; Antoni Sureda (Environmental Toxicology and Pharmacology, 2024)

Plastic webs, the new food: Dynamics of microplastics in a Mediterranean food web, key species as pollution sources and receptors - Ruben Olmo-Gilabert; Valentina Fagiano; Carme Alomar; Beatriz Rios-Fuster; Montserrat Compa; Salud Deudero (Science of The Total Environment, 2024)

Presence and Potential Effects of Microplastics in the Digestive Tract of Two Small Species of Shark from the Balearic Islands - Susana Torres; Montserrat Compa; Antonio Box; Samuel Pinya; Antoni Sureda (Fishes, 2024)
In recent years, there has been an increase in the reporting of plastic pollution in the marine environment and its effects on marine animals, especially bony fish. However, the prevalence and effect, particularly concerning biomarkers of oxidative stress, in elasmobranchs remain underreported and unknown. In this study, microplastics were observed in two elasmobranch species from the Balearic Islands: the small-spotted catshark (Scyliorhinus canicula) with an average of 4.38 ± 1.77 items per individual, and the blackmouth catshark (Galeus melastomus) with an average of 8.31 ± 2.46 items per individual. Moreover, for the first time, antioxidant and pro-inflammatory responses were determined in the digestive tract of individuals of both species. Specifically, the activation of antioxidant defences, mainly superoxide dismutase activity and glutathione levels, was observed, while the pro-inflammatory marker myeloperoxidase activity was also greater in individuals with a high abundance of microplastic items. Additionally, a significant increase in glutathione S-transferase activity in catsharks with high microplastic ingestion was evidenced, suggesting that the detoxification process was activated. Overall, the results of this study highlight that both catshark species are ingesting microplastics, which, in turn, are causing physiological effects at a cellular level. Considering this, continued monitoring of these species should include the presence of microplastics, and the results from this study can serve as baseline data for future research.

Ingestion of microplastics and microfibers by the invasive blue crab Callinectes sapidus (Rathbun 1896) in the Balearic Islands, Spain - Montserrat Compa; Esperança Perelló; Antoni Box; Victor Colomar; Samuel Pinya; Antoni Sureda (Environmental Science and Pollution Research, 2023)
The blue crab Callinectes sapidus Rathbun, 1896 is native to the western coasts of the Atlantic Ocean and is currently considered an invasive species in the Mediterranean Sea. In this study, we examined the stomach contents of C. sapidus to determine the frequency of occurrence of microplastics (MPs) and microfibers (MFs) in the Balearic Islands archipelago in the western Mediterranean Sea. A total of 120 individuals were collected from six locations between 2017 and 2020. Overall, 65.8% of the individuals had MPs and/or MFs particles with an average of 1.4 ± 1.6 particles ind. −1 of which an average of 1.0 ± 1.3 items ind. −1 were MFs and an average of 0.4 ± 0.8 items ind. −1 were MPs. In terms of type, fragments were the dominant type of MPs and the most common size of items ranged from between 0.5 and 1 mm (40%) followed by 1–5 mm (31%). The most prevalent polymers were low-density polyethylene (39%) and high-density polyethylene (26%). In terms of links to human activities, MP ingestion was positively correlated with an increase in drain pipes, whereas MF ingestion was positively correlated with an increase in sewage pipelines, providing evidence of potential sources and the bioavailability of these particles in various environments. This study confirms the widespread presence of MP and MF particles, even in areas that are currently managed under different protection statuses, in the stomach contents of invasive blue crab species throughout coastal communities.

Plastitar in the Mediterranean Sea: New records and the first geochemical characterization of these novel formations - Francesco Saliu; Montserrat Compa; Alessandro Becchi; Marina Lasagni; Elena Collina; Arianna Liconti; Enzo Suma; Salud Deudero; Daniele Grech; Giuseppe Suaria (Marine Pollution Bulletin, 2023)

Stranded and floating marine debris detected along the coastline of Cabrera National Park (Balearic Islands) - Beatriz Rios-Fuster; Montserrat Compa; Carme Alomar; Salud Deudero (Marine Pollution Bulletin, 2023)

Mapping microplastic overlap between marine compartments and biodiversity in a Mediterranean marine protected area - Montserrat Compa; Carme Alomar; Salud Deudero (Science of The Total Environment, 2023)

Sea surface surveys for microplastic and floating marine macro litter items in coastal waters of Cabrera Archipelago Maritime Terrestrial National Park - Montserrat Compa; Carme Alomar; Beatriz Rios-Fuster; Valentina Fagiano; Salud Deudero (Environmental Science and Pollution Research, 2023)
This study is aimed at identifying and comparing microplastics and floating marine litter along the sea surface in the marine protected area of Cabrera Archipelago Maritime Terrestrial National Park (Cabrera MPA) in the Balearic Islands. A total of 52 net surveys and 22 visual surveys were carried out between July and August in 2019 and 2020. The abundance of microplastic (MP) items was highest in the southern and eastern regions, with an average of 381,244.4 ± 1,031,082.8 items/km 2 weighing an average of 927.1 ± 2731.4 g/km 2 . Most of these items were < 5 mm (81%) in size and were mainly composed of polyethylene and polypropylene (98%). In terms of floating marine macro litter (ML) from visual surveys, an average of 2028 ± 2084 items/km 2 were observed. In this case, the majority of the ML items were plastic pieces (69%) measuring 2.5 to 50 cm. Furthermore, ML quantified by visual surveys was an order of magnitude higher than in similar studies carried out on large vessels, highlighting the importance of vessel height and speed for identifying the smallest size fractions (81%). The results of this study document the intensity of MPs and ML, primarily plastic, in coastal waters, and provide a baseline for management efforts to mitigate floating litter, in addition to raising awareness of the transferability of marine litter from other regions.

Are seafloor habitats influencing the distribution of microplastics in coastal sediments of a Marine Protected Area? - Beatriz Rios-Fuster; Montserrat Compa; Carme Alomar; Mercè Morató; Diane Ryfer; Margarita Villalonga; Salud Deudero (Environmental Science and Pollution Research, 2023)
The marine environment is affected by the increasing presence of microplastics (MPs; < 5 mm), and the seafloor acts as a sink for these particles. Locations with different predominant seafloor habitat and protection level applied were selected from Cabrera Marine-Terrestrial National Park (henceforth, Cabrera MPA) (western Mediterranean Sea) with the aim to assess the distribution of MPs along the sediments of this Mediterranean MPA. A total of 37 samples were collected. A high diversity of sediment between locations was detected according to the Udden-Wentworth classification and locations were clustered into two main groups according to the predominance of different particle size fractions. The identification of MPs was carried out according to the sediment particle size classification. A total of 1431 MPs and a mean value (± SD) of 314.53 ± 409.94 items kg −1 D.W. were identified, and 70% of the particles were fibers. Statistically higher abundances of MPs were found in sediments collected from sandy habitats, with a mean value of 630.80 ± 636.87 items kg −1 D.W., compared to the abundances of MPs found in locations with different predominant seafloor habitats, that ranged from 136.79 ± 156.33 items kg −1 D.W. in habitats with similar predominance of seagrass and sand to 223.02 ± 113.35 items kg −1 D.W. in habitats with similar predominance of rocks and sand. The abundance of MPs regarding each sediment particle size fraction differed between years and locations, and the abundance of MPs according to each identified shape differed between sampling years, particle size fraction, and predominant seafloor habitat. The present study highlights the ubiquitous presence of MPs in seafloor sediments from a MPA. Furthermore, the results suggest that the predominant seafloor habitat can modulate the presence of MPs in marine environments in both general abundances and shape of items.